The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13018-018-0730-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural progress of D-dimer following total joint arthroplasty: a baseline for the diagnosis of the early postoperative infection

Abstract: BackgroundEarly detection followed by prompt intervention is essential for the treatment of periprosthetic joint infection (PJI). D-dimer, a fibrin degradation product, characteristically changes rapidly during early postoperative period and has a short half-life. The aim of this prospective study was to measure postoperative change of D-dimer level after joint arthroplasty in conjunction with ESR and CRP.MethodsESR, CRP, and D-dimer levels were measured on the day before surgery, postoperative days 1, 2, 3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 22 publications
2
42
0
4
Order By: Relevance
“…In a prospective, observational clinical study, Ribera et al [33] found that septic joint disease is associated with a marked increase in synovial D-dimer concentration within the affected joint, and synovial D-dimer level may be considered a complementary diagnostic marker of septic joint disease. It has been reported that D-dimer sharply increases up to double levels and decrease to the baseline level within a short time during early postoperative period of TJA, and this dynamic change is more rapid than ESR and CRP [34,35]. Shahi et al [13] found that the sensitivity, specificity, and the cutoff value of plasma D-dimer were 89%, 93%, and 850 ng/mL, respectively, for detecting PJI.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, observational clinical study, Ribera et al [33] found that septic joint disease is associated with a marked increase in synovial D-dimer concentration within the affected joint, and synovial D-dimer level may be considered a complementary diagnostic marker of septic joint disease. It has been reported that D-dimer sharply increases up to double levels and decrease to the baseline level within a short time during early postoperative period of TJA, and this dynamic change is more rapid than ESR and CRP [34,35]. Shahi et al [13] found that the sensitivity, specificity, and the cutoff value of plasma D-dimer were 89%, 93%, and 850 ng/mL, respectively, for detecting PJI.…”
Section: Discussionmentioning
confidence: 99%
“…7 When considering D-dimer levels for the diagnosis of PJI, particular attention should be paid to the natural progress of these levels during the perioperative period. 16 Total joint arthroplasty leads to a state of increased inflammation and coagulation and biomarkers of inflammation such as CRP, ESR, and D-dimer have been shown to have variable values during the postoperative period. Serum D-dimer sharply increases after surgery, reaches a peak at postoperative day 1 (1st peak), then abruptly decreases on day 2, after this it rises slowly till the second week after surgery (2nd peak), and finally, it decreases getting close to normal values at the 6th postoperative week.…”
Section: Periprosthetic Joint Infectionmentioning
confidence: 99%
“…The natural curve of D-dimer is invaluable for the diagnosis of PJI based on abnormal D-dimer levels. 16 Despite all the extraordinary efforts by the orthopaedic community, the diagnosis of PJI remains a challenge. During the last decade, a plethora of markers [17][18][19] have been evaluated for the diagnosis of PJI with recent evidence suggesting that the use of D-dimer might be valuable for that purpose.…”
Section: Periprosthetic Joint Infectionmentioning
confidence: 99%
“…Despite coagulation markers such as Platelet Count and Mean Platelet Volume ratio [22], D-Dimer [23] and plasma Fibrinogen [24] have been used in in ammation and infection diseases diagnosis [10,11], the role of these coagulation markers in PJI diagnosis is still unknow. Although the role of D-Dimer [12][13][14] plasma Fibrinogen [16], Platelet Count and Mean Platelet Volume ratio [15] were evaluated in PJI diagnosis, and D-dimer > 1170 ng/m [14], PC/MPV > 31.70 [15] and FIB > 4.01 µg/mL [16] were recommend as the optimum threshold value for the PJI diagnosis, no subsequent studies were published thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the sensitivity and speci city of several coagulation markers including D-Dimer [12][13][14] Platelet Count and Mean Platelet Volume ratio [15] and plasma Fibrinogen [16] were compared with CRP and ESR in PJI diagnosis, and these studies showed that these commonly used coagulation markers can be selected for PJI diagnosis. However, no subsequent studies were published thereafter.…”
Section: Introductionmentioning
confidence: 99%